2014
DOI: 10.1103/physreva.90.023821
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of double coherent stimulated Raman adiabatic passages in three-levelΛsystems in a cold atomic ensemble

Abstract: Coherent stimulated Raman adiabatic passages (STIRAP) based on a dark state have many applications in diverse quantum systems. In the case of large single-photon detuning in three-level systems, one of the bright states almost does not involve the excited state and then acts as the dark state. In this paper, we report the experimental observation of STIRAP based on the dark state, as well as b-STIRAP based on the above bright state, with the same transfer efficiency in a three-level cold atomic ensemble. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
2
23
1
Order By: Relevance
“…Similar results were demonstrated in Ref. [25] where authors theoretically and experimentally realized a reverse operation for a superposition state ∆P t=0 ab = 0.5 with near-unity fidelity when the required adiabatic condition is fulfilled. Their theoretical study showed a strong oscillation during the intermediate region due to the phase difference between |d and |b 1 while fast oscillations were not clearly observed in practical experiment.…”
Section: Real Dynamics and Propertiessupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results were demonstrated in Ref. [25] where authors theoretically and experimentally realized a reverse operation for a superposition state ∆P t=0 ab = 0.5 with near-unity fidelity when the required adiabatic condition is fulfilled. Their theoretical study showed a strong oscillation during the intermediate region due to the phase difference between |d and |b 1 while fast oscillations were not clearly observed in practical experiment.…”
Section: Real Dynamics and Propertiessupporting
confidence: 87%
“…A perfect switching for the initial populations is revealed with P t m ≈ 0 for the complete evolution. Note that the whole switching time required here is only 4.5 µs, much smaller than that reported in Du's experiment (T = 2ms) [25].…”
Section: Scheme Implementationcontrasting
confidence: 54%
See 1 more Smart Citation
“…STIRAP can coherently transfer population by adiabatically changing a dark state [11][12][13] . The same process is also possible through a bright state (b-STIRAP) 14,15 and both methods have been realized in doped solids 14,[16][17][18] , cold atoms 19 , and quantum dots 20 , to name a few. It has been implemented for coherent manipulation of states 19 in logic operations 21,22 , quantumness witness detection 23 and entanglement generation 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Population transfer by adiabatic evolution is among the most popular methods for coherent atomic manipulation [1][2][3][4][5][6][7][8][9][10]. However, due to the requirement on adiabaticity, the manipulation is very slow.…”
Section: Introductionmentioning
confidence: 99%